5‐HT3A‐driven green fluorescent protein delineates gustatory fibers innervating sour‐responsive taste cells: A labeled line for sour taste?. Issue 10 (21st April 2017) - Stratford, J. M.; Larson, E. D.; Yang, R.; Salcedo, E.; Finger, T. E.
Abstract: Taste buds contain multiple cell types with each type expressing receptors and transduction components for a subset of taste qualities. The sour sensing cells, Type III cells, release serotonin (5‐HT) in response to the presence of sour (acidic) tastants and this released 5‐HT activates 5‐HT3 receptors on the gustatory nerves. We show here, using 5‐HT3A GFP mice, that 5‐HT3 ‐expressing nerve fibers preferentially contact and receive synaptic contact from Type III taste cells. Further, these 5‐HT3 ‐expressing nerve fibers terminate in a restricted central‐lateral portion of the nucleus of the solitary tract (nTS)—the same area that shows increased c‐Fos expression upon presentation of a sour tastant (30 mM citric acid). This acid stimulation also evokes c‐Fos in the laterally adjacent mediodorsal spinal trigeminal nucleus (DMSp5), but this trigeminal activation is not associated with the presence of 5‐HT3 ‐expressing nerve fibers as it is in the nTS. Rather, the neuronal activation in the trigeminal complex likely is attributable to direct depolarization of acid‐sensitive trigeminal nerve fibers, for example, polymodal nociceptors, rather than through taste buds. Taken together, these findings suggest that transmission of sour taste information involves communication between Type III taste cells and 5‐HT3 ‐expressing afferent nerve fibers that project to a restricted portion of the nTS consistent with a crude mapping of taste quality information in the primary gustatory nucleus. Abstract : Confocal image of a longitudinal section through a taste bud showing that nerve fibers expressing the serotonin receptor 5‐HT3A (Green) preferentially contact sour‐responsive Type III taste cells (Red) rather than Type II taste cells (Blue) which respond to other taste qualities.